Crazy rich asians eaudiobook - Kwan, Kevin (Crazy Rich Asians, 2013)
A hilarious and heartwarming New York Times bestselling novel—the basis for the acclaimed major motion picture! "There's rich, there's filthy rich, and then there's crazy rich ... A Pride and Prejudice -like send-up about an heir bringing his Chinese-American girlfriend home to meet his ancestor-obsessed family.” – PEOPLE When New Yorker Rachel Chu agrees to spend the summer in Singapore with her boyfriend, Nicholas Young, she envisions a humble family home and quality time with the man she hopes to marry. But Nick has failed to give his girlfriend a few key details. One, that his childhood home looks like a palace; two, that he grew up riding in more private planes than cars; and three, that he just happens to be the country’s most eligible bachelor.   On Nick’s arm, Rachel may as well have a target on her back the second she steps off the plane, and soon, her relaxed vacation turns into an obstacle course of old money, new money, nosy relatives, and scheming social climbers.